Chemical composition and antibacterial activity of essential oils of Cinnamomum cassia and Syzygium aromaticum plants and their nanoparticles against Erwinia amylovora. (20th January 2022) - Doukkali, Elaaziza; Radouane, Nabil; Tahiri, Abdessalem; Tazi, Bouchra; Guenoun, Farhate; Lahlali, Rachid
ABSTRACT: This study aimed at evaluating the antibacterial activity of Cinnamomum cassia and Syzygium aromaticum essential oils and their nanoparticles (EOs-NPS) against Erwinia amylovora, the causal agent of fire blight disease. First, EOs of C. cassia and S. aromaticum were obtained by hydrodistillation and analysed using a GC–MS/FID. Results showed that the main components of C. cassia EOs are E-Cinnamaldehyde (73.23%), alpha-Copaene (6.44%), and Eugenol (4.23%) while the EOs of S. aromaticum showed the presence of Eugenol (58.64%), β-Caryophyllene (32.91%), and Humulene (3.25%). C. cassia EOs was the most effective with an inhibition zone of 37.7 mm and a minimum bactericidal concentration (MBC) of 1.04%. However, EOs-NPS of C. cassia had greater effects than S. aromaticum with an MBC of 0.75%, rather than the effect of EOs alone. Significant reduction of the disease incidence (86%) was observed in the in vivo pre-treatment using EOs-NPS of C. cassia. Therefore, C. cassia EOs-NPS is recommended against E. amylovora .